Notes of a Commentator: Bulgakov, Esenin, Oleinikov - Oleg A. Lekmanov (Литературный факт, 2021)
The paper offers a selective critical commentary on the three texts of the 1920s: Mikhail Bulgakov’s short story Red Crown, Sergey Esenin’s poem Black Man, Nikolay Oleinikov’s distich Children’s Verses. According to the author of the article, apocalyptic subtext of Bulgakov’s short story defined the room number of the narrator – 27: it corresponds to the number of the Book of Revelation in the New Testament. The source of Esenin’s rhyme “nakoverkala / zerkalo” (deformed / mirror) can be found not in L.A. Mey’s verses (as commentators used to note), but in the biographical stories about Mey, where it is ascribed to the poet N.F. Shcherbina. The author of the article thinks that Oleinikov wrote his verse about the little hare in Kornei Chukovskii’s family almanac re- ferring to the recently published N.K. Chukovskii’s book Animal Cooperative. It explains the choice of the topic and the domestic confinedness of the verse.